A real differential view of equilibrium real exchange rates and misalignments - Mathias Hoffmann; Ronald MacDonald (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper examines the interaction of G7 real exchange rates with real output and interest rate differentials. Using cointegration methods, we generally find a link between the real exchange rate and the real interest differential. This finding contrasts with the majority of the extant research on the real exchange rate - real interest rate link. We identify a new measure of the equilibrium exchange rate in terms of the permanent component of the real exchange rate that is consistent with the dynamic equilibrium given by the cointegration relation. Furthermore, the presence of cointegration also allows us to identify real, nominal and transitory disturbances with only minimal identifying restrictions. Our findings suggest that persistent deviations of real exchange rates from their equilibrium value can have feedback effects on the underlying fundamentals, hence altering the equilibrium exchange rate itself. This has important implications for the persistence measures of real exchange rates that are reported elsewhere in the literature.
urn:nbn:de:hebis:30-9721
Keywords: F31; 330; Equilibrium Exchange Rates; Cointegration; Permanent and Transitory Decomposition